Regional Economic Policy: The Canadian Experience - N. H. Lithwick (American : MC Graw Hill, 1978)
Contents
Part A: Defining the problem: the economics of regional disparties in canada
Part B: The search for solutions: Policies for regional disparities in canada
Keywords: Economics; Canada--economic policy-addresses